Pengaruh Tingkat Leverage (DER) Dan Tingkat Penjualan Terhadap Nilai Perusahaan (PBV) Pada PT Japfa Comfeed Indonesia Tbk Periode 2013 – 2023 - Munadjat, Baliyah; Dwianggoro, Prihadi; Pangaribuan, Hasudungan (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to determine the effect of leverage level (DER) and sales level on firm value (PBV) at PT Japfa Comfeed Indonesia Tbk for the period 2013-2023. The research method used is quantitative with a descriptive approach. Data obtained from the company's financial statements for eleven years and analyzed using multiple linear regression and classical assumption tests. The results showed that partially, DER had no significant effect on PBV, while the level of sales had a significant effect on PBV. Simultaneously, DER and sales level have no significant effect on PBV.